Comparing whole slide digital images versus traditional glass slides in the detection of common microscopic features seen in dermatitis - Nikki S Vyas; Michael Markow; Carlos Prieto-Granada; Sudeep Gaudi; Leslie Turner; Paul Rodriguez-Waitkus; Jane L Messina; Drazen M Jukic (Journal of Pathology Informatics, 2016)
Background: The quality and limitations of digital slides are not fully known. We aimed to estimate intrapathologist discrepancy in detecting specific microscopic features on glass slides and digital slides created by scanning at ×20. Methods: Hematoxylin and eosin and periodic acid-Schiff glass slides were digitized using the Mirax Scan (Carl Zeiss Inc., Germany). Six pathologists assessed 50-71 digital slides. We recorded objective magnification, total time, and detection of the following: Mast cells; eosinophils; plasma cells; pigmented macrophages; melanin in the epidermis; fungal bodies; neutrophils; civatte bodies; parakeratosis; and sebocytes. This process was repeated using the corresponding glass slides after 3 weeks. The diagnosis was not required. Results: The mean time to assess digital slides was 176.77 s and 137.61 s for glass slides (P < 0.001, 99% confidence interval [CI]). The mean objective magnification used to detect features using digital slides was 18.28 and 14.07 for glass slides (P < 0.001, 99.99% CI). Parakeratosis, civatte bodies, pigmented macrophages, melanin in the epidermis, mast cells, eosinophils, plasma cells, and neutrophils, were identified at lower objectives on glass slides (P = 0.023-0.001, 95% CI). Average intraobserver concordance ranged from κ = 0.30 to κ = 0.78. Features with poor to fair average concordance were: Melanin in the epidermis (κ = 0.15-0.58); plasma cells (κ = 0.15-0.49); and neutrophils (κ = 0.12-0.48). Features with moderate average intrapathologist concordance were: parakeratosis (κ = 0.21-0.61); civatte bodies (κ = 0.21-0.71); pigment-laden macrophages (κ = 0.34-0.66); mast cells (κ = 0.29-0.78); and eosinophils (κ = 0.31-0.79). The average intrapathologist concordance was good for sebocytes (κ = 0.51-1.00) and fungal bodies (κ = 0.47-0.76). Conclusions: Telepathology using digital slides scanned at ×20 is sufficient for detection of histopathologic features routinely encountered in dermatitis cases, though less efficient than glass slides.